KONSEP CINTA MENURUT MAHATMA GANDHI - Ni Putu Sinta Oktaviani; Nengah Sukmantara (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Love is one word that is intended to describe the feeling of something that might be liked or liked. In this world no one can escape love, love is a foundation for building a harmonious relationship and one way to achieve happiness. Love is very influential in the joints of life. One of the figures who taught about love and affection is Mohandas K. Gandhi through Ahimsa teachings. Mohandas K. Gandhi or known to Gandhi he was a politician and spiritual leader from India who was involved in the independence movement of India. During his life, Gandhi carried out a struggle to fight violence, namely Ahimsa supported by satyagraha (upholding the truth), he used it in suppressing British rule and recognizing India's independence. In the course of his resistance, he always put forward the values of humanity and moral values. Gandhi's view of anti-violence humans cannot be separated from human understanding, especially humans as social humans who cannot live alone. This study aims to understand about love according to Mohandas K. Gandhi in the teachings of ahimsa whose teachings hold firm to the truth and love by not hurting each other with living beings. By practicing this teaching it is believed that we will always feel happy.